1998
DOI: 10.4141/p97-050
|View full text |Cite
|
Sign up to set email alerts
|

An ecoregional analysis of morphological variation in British Columbia coastal strawberries (Fragaria) for germplasm protection

Abstract: analysis of morphological variation in British Columbia coastal strawberries (Fragaria) for germplasm protection. J. Plant Sci. 78: 117-124. In order to enhance the utilization and protection of wild Fragaria germplasm from coastal British Columbia, patterns of morphological variation were assessed in plants from the Pacific coastal region of Canada. Twenty-five characters were evaluated in 87 plants grown in the uniform garden at the Canadian clonal genebank. Seven characters including the number of veins, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hancock and Bringhurst (1979) suggested that the morphological differences between these species played a major adaptive role in their ecogeographic distribution, especially in regard to water retention and use. It has been suggested that the hybrid might display morphological intermediacy ( Catling and Porebski, 1998b ;Staudt, 1999 ) and reside in an intermediate habitat, yet this has not been broadly tested, nor has a bioclimatic examination of the hybrid zone been undertaken. Moreover, although a previous study with limited sampling revealed that either parent can serve as maternal donor of F. × ananassa subsp.…”
mentioning
confidence: 99%
“…Hancock and Bringhurst (1979) suggested that the morphological differences between these species played a major adaptive role in their ecogeographic distribution, especially in regard to water retention and use. It has been suggested that the hybrid might display morphological intermediacy ( Catling and Porebski, 1998b ;Staudt, 1999 ) and reside in an intermediate habitat, yet this has not been broadly tested, nor has a bioclimatic examination of the hybrid zone been undertaken. Moreover, although a previous study with limited sampling revealed that either parent can serve as maternal donor of F. × ananassa subsp.…”
mentioning
confidence: 99%
“…The anatomy of the leaves varies with the genotype and environment (Jurik et al, 1982;Salamone et al, 2013). Catling and Porebski (1998) studied the morphology of 87 plants of F. chiloensis and F. virginiana from the Pacific coast of Canada. The leaves were rated from thin (index of one) to thick (index of three).…”
Section: Ultrastructure Of the Leavesmentioning
confidence: 99%